Induksi dan Karakterisasi Pisang Mas Lumut Tetraploid - Poerba, Yuyu s; ,, Witjaksono; Ahmad, F.; Handayani, Tri (Perhimpunan Biologi Indonesia, 2014)
Triploid banana breeding could be achieved by crossing tetraploid to diploid banana cultivars. The availaibility of tetraploidbananas is naturally very limited. One of methods to produce tetraploid bananas is inducing tetraploid plants usingchemicals that inhibit spindle fiber formation during mitosis such as oryzalin or colchicine. The present research is aimed toproduce and characterize tetraploid Pisang Mas Lumut (Musa acuminata, AAAA genome) induced by in-vitro oryzalintreatment from diploid Pisang Mas Lumut. Fifteen in vitro-cultured shoots were treated wih oryzalin at of 60ÃÂ¼M for 7days in a liquid MS basal medium with addition of 2 mg/l BA. After 6 sub-cultured, 54 shoots and 104 plantlets wereproduced. Forty seedlings were then survived and grew well and healthy. Ploidy identification of induced Pisang MasLumut was conducted using Flowcytometer at seedling stage and repeated at reproductive phases for 2 cycles. The resultsshowed that oryzalin treatments produced tetraploids at a frequency of 30%, diploid at 65% and mixoploid at 5%. Thetetraploid plants have longer and thicker pseudostems, produce fewer suckers, drooping and larger leaves, and broader fruitscompared to its diploid control at harvest time. The tetraploid plants have similar genetic properties with their diploidcontrols as shown by genetic identity of 0.90-0.97.Key words: Pisang Mas Lumut, Musa acuminata, AA, oryzalin, tetraploid